Whole exome sequencing identified a homozygous novel variant in DOP1A gene in the Pakistan family with neurodevelopmental disabilities: case report and literature review - Wei Zhang; Wei Zhang; Muhammad Tariq; Bhaskar Roy; Juan Shen; Juan Shen; Ayaz Khan; Naveed Altaf Malik; Sijie He; Sijie He; Shahid Mahmood Baig; Xiaodong Fang; et al. (Frontiers in Genetics, 2024)
BackgroundHereditary neurodevelopmental disorders (NDDs) are prevalent in poorly prognostic pediatric diseases, but the pathogenesis of NDDs is still unclear. Irregular myelination could be one of the possible causes of NDDs.Case presentationHere, whole exome sequencing was carried out for a consanguineous Pakistani family with NDDs to identify disease-associated variants. The co-segregation of candidate variants in the family was validated using Sanger sequencing. The potential impact of the gene on NDDs has been supported by conservation analysis, protein prediction, and expression analysis. A novel homozygous variant DOP1A(NM_001385863.1):c.2561A>G was identified. It was concluded that the missense variant might affect the protein-protein binding sites of the critical MEC interaction region of DOP1A, and DOP1A-MON2 may cause stability deficits in Golgi-endosome protein traffic. Proteolipid protein (PLP) and myelin-associate glycoprotein (MAG) could be targets of the DOP1A-MON2 Golgi-endosome traffic complex, especially during the fetal stage and the early developmental stages. This further supports the perspective that disorganized myelinogenesis due to congenital DOP1A deficiency might cause neurodevelopmental disorders (NDDs).ConclusionOur case study revealed the potential pathway of myelinogenesis-relevant NDDs and identified DOP1A as a potential NDDs-relevant gene in humans.